2021
DOI: 10.3390/diagnostics11091619
|View full text |Cite
|
Sign up to set email alerts
|

A New Anatomical Classification for Tibialis Posterior Tendon Insertion and Its Clinical Implications: A Cadaveric Study

Abstract: The variations in the tibialis posterior tendon (TPT) could not be defined by previous classification; thus, this study used a larger-scale cadaver with the aim to classify the types of TPT insertion based on the combination of the number and location of TPT insertions. A total of 118 feet from adult formalin-fixed cadavers were dissected (68 males, 50 females). The morphological characteristics and measurements of TPT insertion were evaluated. Four types of TPT insertions were classified, wherein the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 29 publications
0
4
2
Order By: Relevance
“…In addition, no significant difference by sex or laterality was seen between types. Previous studies have reported different results from this study [ 4 , 5 , 6 , 7 , 8 ]. In particular, previous studies using a similar classification method were 80 feet (European populations) [ 7 ] and 118 feet (Korean populations) [ 8 ], but the results were also different from this study.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…In addition, no significant difference by sex or laterality was seen between types. Previous studies have reported different results from this study [ 4 , 5 , 6 , 7 , 8 ]. In particular, previous studies using a similar classification method were 80 feet (European populations) [ 7 ] and 118 feet (Korean populations) [ 8 ], but the results were also different from this study.…”
Section: Discussioncontrasting
confidence: 85%
“…Previous studies have reported different results from this study [ 4 , 5 , 6 , 7 , 8 ]. In particular, previous studies using a similar classification method were 80 feet (European populations) [ 7 ] and 118 feet (Korean populations) [ 8 ], but the results were also different from this study. Therefore, it was suggested that there is high morphological variability of the TPT in relation to the insertion location, along with the possibility of significant differences according to race and gender.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations